Analisis Emotional branding Visualisasi Iklan Televisi Yamaha Fazzio Hybrid-Connected - Dian Eka Permanasari (Kalijaga Journal of Communication, 2022)
This study analyzes emotional branding in the visualization of Yamaha Fazzio Hybrid-Connected television commercials. This study applies a qualitative-descriptive method with the approach of Marc Gobe's emotional branding theory. The results of the study show that visualization of Yamaha Fazzio Hybrid-Connected advertisements seeks to build emotional branding through a series of strategies such as building relationships with consumers, multi-sensory experiences, affirming vision, and imagination to establish communication with consumers as self-actualization.